Association of ejection fraction with mortality and cardiovascular events in patients with coronary artery disease. (21st July 2022) - Liu, Yupeng; Song, Jingjing; Wang, Wenyao; Zhang, Kuo; Qi, Yu; Yang, Jie; Wen, Jun; Meng, Xiangbin; Gao, Jun; Shao, Chunli; Tang, Yi‐Da
Abstract: Aims: Recent studies suggested that both left ventricular ejection fraction (LVEF) lower than 60% or higher than 65% were associated with an increased mortality in the general population. Uncertainty remains regarding adverse outcomes across LVEF in coronary artery disease (CAD). The common understanding was that LVEF <40% was associated with an increased risk of mortality. But the threshold at LVEF of 40% was arbitrary because quite a lot of adverse outcomes existed in patients with ejection fraction >40%. We aimed to evaluate the relationship between LVEF and mortality or adverse events in CAD patients undergoing percutaneous coronary intervention (PCI). Methods and results: A total of 10 252 CAD patients undergoing PCI from an observational cohort were studied. All‐cause mortality and major adverse cardiovascular and cerebrovascular events (MACCE) were set as outcomes. Kaplan–Meier curves, adjusted Cox regression models, and restricted cubic spline analyses were used for evaluation. A total of 137 (1.3%) patients had all‐cause mortality, and 816 (8.0%) patients had MACCE during a median of 2.4 years of follow‐up. The median LVEF was 64%. All‐cause mortality and MACCE rates changed substantially across LVEF categories, and a linear inverse relationship of LVEF with all‐cause mortality and MACCE risk was observed. All‐cause mortality or MACCE risk increased significantly below an LVEF of 55 or 65%, respectively. Patients with LVEF <55% had a more than 3.5‐fold higher mortality than those with LVEF ≥55%. Patients with LVEF <65% had a more than 1.3‐fold higher MACCE than those with LVEF ≥65%. Below 55 or 65%, there was a rise in mortality or MACCE. A gradient–response relationship was observed, with an all‐cause mortality risk range between 8.6‐fold and 3.0‐fold increase from LVEF <40 to 50–54.9% and MACCE risk range between 2.4‐fold and 1.4‐fold from LVEF <40 to 60–64.9%. Conclusions: In CAD patients undergoing PCI, LVEF lower than 55% or LVEF lower than 65% was correlated with increased all‐cause mortality and MACCE respectively, whereas higher LVEF was not.